Digital image compression for graphics data - Zhang, Junlin (2009)
This project highlights how normal mapping affects various digital image or data compression methods for graphics data. It also shows how normal maps can help to restore an image quality and integrity without experience significant loss. The project used two digital image compression methods to illustrate the effects of normal mapping on two dimensional texture images. The two compression methods used are: 1. Block Truncation Coding 2. Discrete Cosine Transformation (DCT / JPEG) The two different image compression methods results are analyzed and discussed together with and without normal mapping application.